PERENCANAAN STRUKTUR GEDUNG POLITEKNIK KESEHATAN SEMARANG - Muhammad Irvan Zidny; Whanda Aristia Widiyanto; Ilham Nurhuda; Himawan Indarto (Jurnal Karya Teknik Sipil, 2015)
Structure design of Semarang Health Polytechnic building was designed with SNI 2847-2013 and SNI 1726-2012, Semarang Health Polytechnic building structures was included in Seismic Design Criteria Type D with high seismic risk level, so in designing the building used special moment resisting frames system method. It also used the concept of capacity design. The purpose of this concept if the strong earthquake is occur, plastic hinges can be formed on the element beams structure. In order to ensure plastic hinges are formed on the beams, the columns should be designed to be stronger than the beams (Strong Column Weak Beam). The foundation was designed as caisson foundation, because the soil in that area was hard soil type. The results of the structural analysis show that the building was safe analytically.